An evaluation of the range-gated-imaging technology under dense aerosol environments - Cho, J.W.; Choi, Y.S.; Jeong, K.M. (Opto-Electronics Review, 2018)
Range-gated-imaging system, which can be used to eliminate backscatter in strong scattering environments, is based on two high speed technologies. It uses high power, ultra-short pulse laser as the light source. And it opens the optical gate of an ICCD camera with a micro-channel-plate image intensifier in a very short time while the laser pulses reflected by the object is coming back to the ICCD camera. Using this range-gated-imaging technology, the effect of scattered light can be reduced and a clear image is obtained. In this paper, the test results of the range-gated-imaging system under dense aerosol environments, which simulates environments in the reactor containment building when the severe accident of the nuclear power plant occurred, are described. To evaluate the observation performance of the range-gated-imaging system under such dense fog environment, we made a test facility. Fog particles are sprayed into the test facility until fog concentration is reached to the postulated concentration level of the severe accident of the nuclear power plant. At such dense fog concentration conditions, we compared and evaluated the observation performances of the range-gated-imaging system and the CCD camera.